2020
DOI: 10.32598/irjns.6.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Urge to Operate: One-year Neurophysiological Follow-up in Severe CTS

Abstract: Background and Aim: Several approaches have been proposed for the treatment of Carpal Tunnel Syndrome (CTS) based on its severity. The aim of this study is to determine the optimal management for severe CTS. Methods and Materials/Patients: This cross-sectional study was conducted for 22 months from August 2017 to June 2019 in a referral rehabilitation clinic in southern Iran. A total of 117 hands diagnosed with severe CTS were included in 78 patients according to Electrodiagnostic Study (EDX) reports (consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…SNAP or CMAP amplitude was not typically discussed, which may be because the primary diagnostic criteria for CTS centered on DML and DSL, and the improvement in these parameters can indicate a change in CTS severity. Ashraf et al (2020) reported that SNAP appeared in 63% of patients with severe CTS after an initial absence of SNAP following a 1-year follow-up electrodiagnostic study. Furthermore, in patients with low SNAP findings, SNAP amplitude and sensory latency at the wrist showed significant improvement ( Ashraf et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SNAP or CMAP amplitude was not typically discussed, which may be because the primary diagnostic criteria for CTS centered on DML and DSL, and the improvement in these parameters can indicate a change in CTS severity. Ashraf et al (2020) reported that SNAP appeared in 63% of patients with severe CTS after an initial absence of SNAP following a 1-year follow-up electrodiagnostic study. Furthermore, in patients with low SNAP findings, SNAP amplitude and sensory latency at the wrist showed significant improvement ( Ashraf et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“… Ashraf et al (2020) reported that SNAP appeared in 63% of patients with severe CTS after an initial absence of SNAP following a 1-year follow-up electrodiagnostic study. Furthermore, in patients with low SNAP findings, SNAP amplitude and sensory latency at the wrist showed significant improvement ( Ashraf et al, 2020 ). Therefore, we suggest that the increase in SNAP amplitude in this study may be indicative of an early neurophysiological improvement; however, this requires further investigation.…”
Section: Discussionmentioning
confidence: 99%